Migrant Smuggling on the Borders of Northern Chile: Migratory Irregularization and its Resistance - Liberona Concha, Nanette (2022)
This article seeks to account for the link between Chilean migration policies and the production of migrant smuggling on the country’s northern borders, in a context of global migration regime. Likewise, it reflects on the consequences of migratory illegalization caused by migrant smuggling and by the elaboration and legitimization of categories such as illicit, crime and irregular. To this end, a review of the literature referring to illegalized migration is made, taking some elements of the autonomy of migrations. It is evident that citizenship is exercised if social rights are assured, which is not the case with this population, that experiences a hyper vulnerability of its life, but that at the same time puts into practice a series of clandestine and public, individual and collective resistance that allows them to exercise a migrant citizenship. Methodologically, an ethnography of migrant smuggling was carried out at the border crossing to Chile between 2018 and 2021, which was complemented with a press review through the categorization of news from 2016 to 2021; and interviews with institutional informants were also conducted. It is concluded that migrant smuggling plays an important role in the illegalization of the migrant population, however, the conditions in which it occurs should be considered in judicial processes, since it would be aggravated trafficking. Considering it this way, it should lead to the regularization of migrants; nevertheless, they are criminalized instead, treated as “illegal” and have been subject to collective expulsions that, paradoxically, were analyzed as illegal.